America's war for the greater Middle East : a military history - Bacevich, Andrew J. (New York : Random House, 2017)
From the end of World War II until 1980, virtually no American soldiers were killed in action while serving in the Greater Middle East. Since 1990, virtually no American soldiers have been killed in action anywhere else. What caused this shift? Andrew J. Bacevich, one of the country's most respected voices on foreign affairs, offers an incisive critical history of this ongoing military enterprise--now more than thirty years old and with no end in sight. During the 1980s, Bacevich argues, a great transition occurred. As the Cold War wound down, the United States initiated a new conflict--a War for the Greater Middle East--that continues to the present day. The long twilight struggle with the Soviet Union had involved only occasional and sporadic fighting. But as this new war unfolded, hostilities became persistent. From the Balkans and East Africa to the Persian Gulf and Central Asia, U.S. forces embarked upon a seemingly endless series of campaigns across the Islamic world. Few achieved anything remotely like conclusive success. Instead, actions undertaken with expectations of promoting peace and stability produced just the opposite. As a consequence, phrases like "permanent war" and "open-ended war" have become part of everyday discourse. Connecting the dots in a way no other historian has done before, Bacevich weaves a compelling narrative out of episodes as varied as the Beirut bombing of 1983, the Mogadishu firefight of 1993, the invasion of Iraq in 2003, and the rise of ISIS in the present decade. Understanding what America's costly military exertions have wrought requires seeing these seemingly discrete events as parts of a single war. It also requires identifying the errors of judgment made by political leaders in both parties and by senior military officers who share responsibility for what has become a monumental march to folly. This Bacevich unflinchingly does.--From dust jacket.
Preliminaries -- War of choice -- Gearing up -- Arsenal of theocracy -- Silver screen six Is calling -- Mad dog, kicked, bites back -- Rescuing evil -- No clean ending -- Entr'acte -- Good intentions -- Balkan digression -- What winning means -- Phony war -- Main card -- Changing the way they live -- Kicking down the door -- How this ends -- Government in a box -- Entropy -- Iraq, again -- Generational war.
Includes bibliographical references (pages 373-430) and index.
Keywords: 1900-2099; Diplomatic relations; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States; United States -- History, Military -- 20th century; United States -- History, Military -- 21st century; Middle East; United States; Military history